Sexual Function in Renal Transplant Recipients with Internal versus External Iliac Artery Anastomosis: A Randomized Clinical Trial - Javid, Amir; Saberi, Narjes; Behnamfar, Amir; Gharzi, Hosna; Gholipour, Farshad; Bahrami, Hossien (Urology Journal, 2024)
Purpose: The choice between using the internal or external iliac arteries to supply a transplanted kidney poses a dilemma during renal transplantation. As the internal iliac artery branches to the genital tract, cutting it could potentially result in sexual dysfunction. The purpose of this study was to compare the effects of these two surgical methods on sexual function. Materials and Methods: 122 sexually active male patients under the age of sixty were randomly divided into two groups: the internal iliac anastomosis group and the external iliac artery anastomosis group. Before surgery and one year after the procedure, patients completed the International Index of Erectile Function-15 questionnaire (IIEF- 15), and the difference in scores of each domain was measured. Results: Statistically, kidney transplantation improved all domains of IIEF in both groups, except for erectile function in patients who underwent internal iliac artery anastomosis group. Additionally, there were significant differences between the two groups in the domains of erectile function (p-value=0.04) and overall satisfaction (p-value = 0.002), while other domains such as orgasmic function, sexual desire, and intercourse satisfaction did not show any statistically significant differences. Conclusion: In conclusion, the choice between using the internal or external iliac artery for arterial anastomosis during kidney transplantation does not significantly impact graft function. However, it may negatively affect erectile function in patients who undergo internal iliac artery anastomosis.